The effect of white matter hyperintensities on verbal memory: Mediation by temporal lobe atrophy. (20th February 2018) - Swardfager, Walter; Cogo-Moreira, Hugo; Masellis, Mario; Ramirez, Joel; Herrmann, Nathan; Edwards, Jodi D.; Saleem, Mahwesh; Chan, Parco; Yu, Di; Nestor, Sean M.; Scott, Christopher J.M.; Holmes, Melissa F.; et al.
Abstract : Objective: To determine the relationship between white matter hyperintensities (WMH) presumed to indicate disease of the cerebral small vessels, temporal lobe atrophy, and verbal memory deficits in Alzheimer disease (AD) and other dementias. Methods: We recruited groups of participants with and without AD, including strata with extensive WMH and minimal WMH, into a cross-sectional proof-of-principle study (n = 118). A consecutive case series from a memory clinic was used as an independent validation sample (n = 702; Sunnybrook Dementia Study; NCT01800214). We assessed WMH volume and left temporal lobe atrophy (measured as the brain parenchymal fraction) using structural MRI and verbal memory using the California Verbal Learning Test. Using path modeling with an inferential bootstrapping procedure, we tested an indirect effect of WMH on verbal recall that depends sequentially on temporal lobe atrophy and verbal learning. Results: In both samples, WMH predicted poorer verbal recall, specifically due to temporal lobe atrophy and poorer verbal learning (proof-of-principle −1.53, 95% bootstrap confidence interval [CI] −2.45 to −0.88; and confirmation −0.66, 95% CI [−0.95 to −0.41] words). This pathway was significant in subgroups with (−0.20, 95% CI [−0.38 to −0.07] words, n = 363) and without (−0.71, 95% CI [−1.12 to −0.37] words, n = 339) AD. Via the identical pathway, WMH contributed to deficits in recognition memory (−1.82%, 95% CI [−2.64% to −1.11%]), a sensitive and specific sign of AD. Conclusions: Across dementia syndromes, WMH contribute indirectly to verbal memory deficits considered pathognomonic of Alzheimer disease, specifically by contributing to temporal lobe atrophy.